Risk Factors for Adolescent Pregnancy in the New Normal Era of the Covid-19 Pandemic: A Case-Control Study - Qurniyawati Eny; Martini Santi; Syahrul Fariani; Sari Dewi Maya; Lubis Rahayu; Mohamed Gomaa Nasr Nayla (BIO Web of Conferences, 2022)
Cases of early marriage are reported to have increased during the pandemic due to stressed teenagers with the pressure of online learning. The increase in this number plays a role in increasing the risk of teenage pregnancy. This study aimed to analyse the risk factors for adolescent pregnancies during the new normal era of the COVID-19 pandemic. A case-control design using a simple random sampling technique involved 40 pregnant adolescents aged 15-19 years and 80 non-pregnant adolescents during the online learning period (July 2021 to January 2022) in Ngawi Regency, Indonesia. Data obtained from interviews were analysed to find Odds Ratio (OR) with a 95% Confidence Interval (CI). Results showed factors associated with adolescent pregnancies were underpaid parental income (OR 4.00, 95%CI 1.64–9.74), authoritarian and permissive parenting (OR 12.75, 95%CI 4.71–34.46), lack of exposure to media about reproductive health (OR 7.91, 95%CI 3.32–18.84), risky dating behaviour (OR 37.09, 95%CI 4.86–283.25), and smoking habit (OR 5.57, 95%CI 1.03–30.12). Preventing adolescent pregnancies could be done through public health education focusing on adolescent communities, parent-child discussion on reproductive health, as well as exposure to educative media related to reproductive health and the impacts of juvenile delinquency.